Biochar and Fulvic Acid to Activate Soil Fertility for Achieving Agro-ecology Benefits in a Newly Reclaimed Coastal Wetland of China - Yang, Rongjiang Yao, Yunpeng Sun, Jinsong; Chen, Xiaobing (Emirates Journal of Food and Agriculture, 2019)
Reclamation of coastal tidal flat lands for obtaining more lands has lasting for many years in China. More attention should be paid on soil and water pollution for protecting coastal ecosystem during the period of saline soil amelioration. A field experiment was conducted for two years in eastern China to investigate the effects of different rates of biochar (BC) (at 0, 7.5, and 30 t ha-1) and/or fulvic acid (FA) (at 0, 0.075 t ha-1) with/without nitrogen (N) fertilizer on the soil physical, chemical, and nutritional properties, as well as crop yield, with a maize-barley rotation. Results showed that N application caused soil compaction, and BC+FA treatments decreased soil bulk density (ranging from 1.22 to 1.28 g cm3) and improved water retention under the condition. Extreme precipitation accelerated soil de-salinization during the crop cultivation (soil EC decreased to the low value ranging from 127 to 141 μS cm-1, after maize harveseted). N addition improved grain yield of maize (increased by 105% under BC30+FA+N, compared with the CK treatment), but there was no significant difference between the N and no-N added treatments. However, the grain yield and straw weight of barley in with-N treatments were twice as much as those of the no-N treatments. The soil nutrion contents (total nitrogen and phosphorus content) after maize and barley crops were higher, under no-N treatments compared to the with-N treatments. A lower pH (8,78) and higher Ca2+ + Mg2+ content (0.24 ~ 0.26 g kg-1) existed in BC30+FA treated plots after maize and barley crops. Replacement of nitrogen fertilizer by BC and FA in the coastal saline soil was feasible in a short time. Therefore, nitrogen fertilizer usage should be regulated for protecting the coastal ecology system, and also achieving agricultural benefits.